2004
DOI: 10.4049/jimmunol.172.8.4926
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Blood Stage Parasites Activate Human Plasmacytoid Dendritic Cells and Murine Dendritic Cells through a Toll-Like Receptor 9-Dependent Pathway

Abstract: A common feature of severe Plasmodium falciparum infection is the increased systemic release of proinflammatory cytokines that contributes to the pathogenesis of malaria. Using human blood, we found that blood stage schizonts or soluble schizont extracts activated plasmacytoid dendritic cells (PDCs) to up-regulate CD86 expression and produce IFN-α. IFN-α production was also detected in malaria-infected patients, but the levels of circulating PDCs were markedly reduced, possibly because of schizont-stimulated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
220
2
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(242 citation statements)
references
References 41 publications
13
220
2
5
Order By: Relevance
“…Given these findings, hemozoin, a known parasite ligand for TLR9, is a possible candidate ligand. Hemozoin is abundant in pRBCs, and it does not induce IFN-␣ production upon stimulation of DCs (31). Indeed, hemozoin-related immune suppression has been previously reported (50).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Given these findings, hemozoin, a known parasite ligand for TLR9, is a possible candidate ligand. Hemozoin is abundant in pRBCs, and it does not induce IFN-␣ production upon stimulation of DCs (31). Indeed, hemozoin-related immune suppression has been previously reported (50).…”
Section: Discussionmentioning
confidence: 95%
“…TLR7 recognizes single-stranded RNA from viruses (23), while TLR9 recognizes DNA containing unmethylated CpG motifs (24). Recently, some reports have found that malaria parasites express molecules that are recognized by TLR9 (31,32), suggesting that TLR9 is a much more likely candidate. To confirm this, we conducted studies using mice lacking TLR7 or TLR9.…”
Section: Tlr9 Signaling In Dcs Is Required For Treg Activationmentioning
confidence: 99%
“…These results provide the first evidence that malarial Prx associates directly with TLR4. Recently, glycosyl phosphatidylinositol (GPI) [9] and hemozoin derived from Plasmodium parasites [10,11] have been identified as the ligands for TLR2 and TLR9, respectively. However, regarding TLR4 ligands in malarial studies, so far, there is no reported evidence.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not observe significant differences in parasitemia between TLR4 -/-and WT (data not shown). Since recent reported evidences indicate that glycosyl phosphatidylinositol (GPI) [9] and hemozoin derived from Plasmodium parasites [10,11] participate in innate immune responses in murine malaria, these findings might suggest that other malarial molecules also will be involved in the induction of innate resistance in murine malaria. To clarify whether malarial Prx induces a complete protective immunity in malaria or not, further experiments will be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple innate-sensing pathways were shown to mediate type I IFN induction by the parasite. In addition to TLR7/TLR9-dependent mechanisms (160,161), type I IFNs can be induced in a STING, TBK1, IRF3/IRF7-dependent manner via AT-rich stem-loop DNA (162). P. berghei-derived RNA also can trigger IFN-b production in a melanoma differentiation-associated protein 5/MAVS-dependent manner (163).…”
Section: Plasmodiummentioning
confidence: 99%